An Overview of Thermal Analysis of Polymers - DR Hardy Chan Sze On (ASEAN Journal on Science and Technology for Development, 1986)
This article presents an up-to-date overview of the application of thermoanalytical methods in the study of polymers with special focus on thermogravimetry, differential thermal analysis, diferential scening calorimetry and thermomechanical analysis. The working principles behind the variouse thermoanalytical methods together with modes of operation are described. Their usefulness in the characterisation of polymers is cowered comprehensively with examples cited in the litearture. The question of validity of data obtained from thermokinetic studies of polymers is examined and it is felt that the kinetic parameters generated carry little physical meaning about the kinetic of the polymer reaction.